STUDI PUSTAKA: KEJAYAAN MAJAPAHIT MASA PEMERINTAHAN RAJASANAGARA - Nata Hudin, Mukhlisin; Susanti, Retno; Hudaidah, Hudaidah (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2025)
Majapahit was a religious kingdom. This research aims to find out the glory of Majapahit during the reign of Rajasanagara, socio-economic life, and know the acculturation of Majapahit culture. The research method used is descriptive qualitative in the form of literature review obtained from articles, journals, books, research reports, proceedings, theses and so on. This research produced a description of the Majapahit kingdom which reached its peak during the reign of Rajasanagara, the socio-economic life at that time and cultural acculturation in the form of religious literature and sacred buildings. The Majapahit Kingdom reached its peak during the reign of Hayam Wuruk or Rajasanagara. Majapahit implemented a well-structured government system. Majapahit built strong diplomatic relations with various kingdoms, including China, Champa, Siam and India. Based on the records of Chinese traveler Ma-Huan, the economic system of Majapahit society was believed to be relatively advanced during the reign of Rajasanagara. As a Hindu-Buddhist kingdom. Majapahit emphasized religious life marked by artifacts and textual remains. Majapahit literature was always acculturated with the religious system which eventually formed its own culture for the Majapahit kingdom. The form of acculturation is implemented in Majapahit's sacred buildings that are based on religious teachings.